The intention to participate in the boycott movement among university students - Lim, Fang Chiang; Muhammad Arif, Afida Mastura (HRMARS, 2024)
People engage in the boycott movement to show their deep disapproval of a company's or government's behaviour and regulations. Despite the rise in consumer boycotts, little attention has been given on the psychological and motivational factors that drive consumer boycott behaviour among university students in a multicultural and multi-ethnic religious society. In response to this gap, and with the support of an extended version of the Theory of Planned Behaviour, this study investigates how attitude, subjective norms, perceived behavioral control, animosity and religious belief are related to the boycott intentions among the students in one university in Malaysia. This study utilized simple random sampling to select 265 respondents. The collected data was analyzed using descriptive statistics, Pearson's coefficient correlation, and multiple linear regression. Multiple regression analysis revealed that all of these variables are related to the boycott intentions among university students, with attitude being identified as the most significant factor influencing the boycott intention. The findings of the study provide a better understanding of why university students want to participate in a boycott against specific businesses. In addition, the study has suggested several positive implications for various groups, including businesses, consumers, as well as governmental and non-governmental organisations.